2002
DOI: 10.1002/cncr.10722
|View full text |Cite
|
Sign up to set email alerts
|

Transitional cell metaplasia of the uterine cervix is related to human papillomavirus

Abstract: BACKGROUND. Transitional cell metaplasia of the uterine cervix is an under-recognized entity in cervical pathology. The underlying etiology and biologic significance remains uncertain. The thin-layer cytology findings and association with human papillomavirus (HPV) have not been studied thoroughly. METHODS. The authors retrospectively reviewed the clinical findings, thin-layer cytology and histologic features of pure transitional cell metaplasia of the uterine cervix occurring in seven perimenopausal or postme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The majority of the biopsies showing discrepancies in Histology 2a vs 2b presents small areas of metaplastic atypia, difficult to fit into the CIN groups (Geng et al, 1999;Montes et al, 1999;Ng et al, 2002;Zuna et al, 2002). The discrepancy in the relative frequency of 'normals' between Histology 2a and 2b is due to the fact that in 2b the emphasis was on representativeness for the transformation zone.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the biopsies showing discrepancies in Histology 2a vs 2b presents small areas of metaplastic atypia, difficult to fit into the CIN groups (Geng et al, 1999;Montes et al, 1999;Ng et al, 2002;Zuna et al, 2002). The discrepancy in the relative frequency of 'normals' between Histology 2a and 2b is due to the fact that in 2b the emphasis was on representativeness for the transformation zone.…”
Section: Discussionmentioning
confidence: 99%
“…Human papillomavirus (HPV) is an oncogenic virus that is strongly associated with squamous cell dysplasia of female uterine cervix and its progression to cervical carcinoma. Cervical transitional cells in the squamocolumnar junction are well‐known targets for HPV infection and potential cancerous transformation 1 . It has also been suggested that the progenitor cells in esophageal squamous cell carcinoma (ESCC) and possibly Barrett's esophagus (BE) resemble those of cervical cancer 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Cervical transitional cells in the squamocolumnar junction are well-known targets for HPV infection and potential cancerous transformation. 1 It has also been suggested that the progenitor cells in esophageal squamous cell carcinoma (ESCC) and possibly Barrett's esophagus (BE) resemble those of cervical cancer. 2,3 Given these similarities and the possibility of HPV exposure to the upper gastrointestinal (GI) tract through oral transmission, HPV has been examined as a possible risk factor for esophageal cancer as well as BE.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Most of the TCM express the urothelial immunophenotype Cytokeratin 7 and 20; this fact supports the former theory. [18] The factors responsible at the gene level for expression of this cell type are not known.…”
Section: Discussionmentioning
confidence: 99%